Metal–organic framework structure–property relationships for high-performance multifunctional polymer nanocomposite applications. Issue 8 (23rd February 2021) - Unnikrishnan, Vishnu; Zabihi, Omid; Ahmadi, Mojtaba; Li, Quanxiang; Blanchard, Patrick; Kiziltas, Alper; Naebe, Minoo
Abstract : Metal–organic frameworks (MOFs) have emerged as a new class of crystalline nanomaterials with ultrahigh porosities and high internal surface areas. Abstract : Metal–organic frameworks (MOFs) have emerged as a new class of crystalline nanomaterials with ultrahigh porosities and high internal surface areas. Recently, these MOF structures with their extraordinary inherent properties have become potential candidates for specific technologies in areas such as the automotive, defence, and aerospace industries. Conversely, polymeric materials are common in a wide variety of industrial applications due to their unique properties and versatile performance. The idea of hybridising MOFs and polymers purely for their distinct superior properties has led to the concept of hybrid composite structures, which exhibit the inherent properties of the two different materials. However, MOFs by themselves have always been considered as labile reinforcements for polymers to afford multifunctional nanocomposites. Therefore, to improve the interactions between MOFs and polymers, it is imperative to understand the factors affecting the inherent MOF properties. This review briefly presents approaches for the synthesis, functionalisation, and post-synthesis modification of MOFs, and the opportunities and challenges for the utilisation of MOFs in high-performance, multifunctional polymer nanocomposites are comprehensively reviewed. In this regard, a wide range of properties related to multifunctional polymer nanocomposites, with a focus on mechanical properties and flame retardancy, are presented. Recent trends in the hybridisation of MOFs with various substrates and other two-dimensional nanomaterials such as graphene and boron nitrides are also discussed. This review highlights the potential of MOFs as versatile porous materials for the development of novel hybrid fillers which could represent remarkable advances in the field of high-performance multifunctional composites.